1993
DOI: 10.1046/j.1365-313x.1993.t01-9-00999.x
|View full text |Cite
|
Sign up to set email alerts
|

PCR‐amplified microsatellites as markers in plant genetics

Abstract: SummaryIn order to assess the feasibility of using microsatellites as markers in plant genetics, a survey of published DNA sequence data for presence, abundance and ubiquity in higher plants of all types of dinucleotide and trinucleotide repeats with a minimum number of 10 and 7 units, respectively, was conducted. This search revealed that such microsatellites are frequent and widely distributed; they were uncovered in 34 species, with a frequency of one every 50 kb. AT repeats were by far the most frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
160
1
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(175 citation statements)
references
References 30 publications
(15 reference statements)
12
160
1
2
Order By: Relevance
“…Apricot diversity and genetic relationships have been studied using isozymes (Byrne and Littleton, 1989;Badenes et al, 1996), restriction fragment length polymorphisms (RFLPs) (De Vicente et al, 1998), random amplified polymorphic DNA (RAPDs) (Badenes et al, 2000), amplified fragment length polymorphisms (AFLPs) (Hagen et al, 2002;Hurtado et al, 2002) and sequence characterised amplified regions (SCARs) (Mariniello et al, 2002). However, most of these early types of molecular markers have been displaced by others, such as microsatellites (simple sequence repeat, SSR) -which are co-dominant and offer significant advantages in terms of reproducibility and simplicity (Morgante and Olivieri, 1993). There is already a considerable literature related to the use of microsatellites in the study of genetic relationships in apricot (Hormaza, 2001(Hormaza, , 2002Romero et al, 2003;Zhebentyayeva et al, 2003;Sánchez-Pérez et al, 2004;Krichen et al, 2006;Tian-Ming et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Apricot diversity and genetic relationships have been studied using isozymes (Byrne and Littleton, 1989;Badenes et al, 1996), restriction fragment length polymorphisms (RFLPs) (De Vicente et al, 1998), random amplified polymorphic DNA (RAPDs) (Badenes et al, 2000), amplified fragment length polymorphisms (AFLPs) (Hagen et al, 2002;Hurtado et al, 2002) and sequence characterised amplified regions (SCARs) (Mariniello et al, 2002). However, most of these early types of molecular markers have been displaced by others, such as microsatellites (simple sequence repeat, SSR) -which are co-dominant and offer significant advantages in terms of reproducibility and simplicity (Morgante and Olivieri, 1993). There is already a considerable literature related to the use of microsatellites in the study of genetic relationships in apricot (Hormaza, 2001(Hormaza, , 2002Romero et al, 2003;Zhebentyayeva et al, 2003;Sánchez-Pérez et al, 2004;Krichen et al, 2006;Tian-Ming et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…human (Weissenbach et al, 1992), mouse (Copeland et al, 1993), cattle (Bishop et al, 1994) and pig (Rohrer et al, 1994). This simple sequence repeats are also abundant in many important crops (Morgante & Olivieri, 1993), and were found to be more polymorphic than RFLP markers when small numbers of MS were investigated in soybean, rice, Arabidopsis or barley (Akkaya et al, 1992;Wu & Tanksley, 1993;Bell & Ecker, 1994;Maroof et al, 1994). Microsatellites as a marker system have the potential to be especially useful for selfpollinating crops like wheat due to their high level of polymorphism based on different numbers of repeats in different lines/accessions at a given locus.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerase chain reaction studies have revealed that microsatellite sequences in several plant genes are polymorphic in their length [4,9]. In addition, the The nucleotide sequence data reported will appear in the EMBL, GenBank and DDBJ Nucleotide Sequence Databases under the accession numbers L12393 (pBSK1) and L12394 (pBSK2).…”
mentioning
confidence: 99%